HIV incidence and compliance with deferral criteria over three progressively shorter time deferrals for men who have sex with men in Canada. Issue 1 (1st December 2021) - Caffrey, Niamh; Goldman, Mindy; Osmond, Lori; Yi, Qi‐Long; Fan, Wenli; O'Brien, Sheila F.
Abstract: Background: In Canada, the deferral for men who have sex with men (MSM) has been progressively reduced from a permanent deferral for MSM since 1977, to 5 years, 1 year, and, most recently, 3 months. We estimated human immunodeficiency virus (HIV) residual risk and compliance with the MSM time deferral after each change. Methods: Four anonymous online compliance surveys were carried out before and after each change. HIV incidence and prevalence were monitored from 2010 to 2021. Residual risk was estimated using the incidence‐window period model. Results: Human immunodeficiency virus prevalence, incidence, and residual risk did not change with incrementally shorter MSM deferrals. The residual risk per million donations post 3‐month deferral was 0.05 (0.001–0.371). Men with temporally remote MSM history became eligible and, therefore, compliant as the deferral periods decreased (Cochran‐Armitage p value = <.0001). However, the percentage of men with MSM history in the last 3 months with the indefinite deferral in place was similar to the percentage noncompliant, while the 3‐month deferral was in place. MSM donors did not report high‐risk behaviors for which they would otherwise be deferred in any survey. Following the change, an estimated 4467 MSM per year were eligible to donate, an increase from 2501 estimated eligible MSM donors following the change to the 1‐year deferral. Conclusion: With progressively shorter MSM deferral periods, HIV residual risk was unchanged. The proportion of male donors with deferrable MSM history remained low, while those with temporally remote MSM history became eligible, increasing the number of eligible MSM donors.